Improving Vocabulary Mastery Through the Vocabulary Self-Collection Strategy (VSS): A Case of Junior High School Students - Nispa Ramadani; Nadrun Nadrun; Moh Abraham Akbar Eisenring; Abd. Kamaruddin (Journal of General Education and Humanities, 2025)
This study aimed to investigate whether the Vocabulary Self-Collection Strategy (VSS) could improve the vocabulary mastery of the eighth-grade students at SMP Negeri 4 Palu. A quasi-experimental design involving pre-test and post-test control groups was employed. The population consisted of all eighth-grade students, with two classes selected through purposive sampling: class VIII APEL, serving as the experimental group, was taught using VSS (n = 32), and class VIII RAMBUTAN, serving as the control group, employed the conventional method (n = 30). The study focused on students’ understanding of word meanings and their use of two high-frequency lexical categories: common nouns and action verbs. The data collected were analysed using descriptive statistics and an independent sample t-test, employing a 0.05 significance level. The results showed an improvement in the experimental group, whose mean score increased from 51.8 in the pre-test to 80 in the post-test, while the control group improved only from 54.8 to 63.3. The t-test result, t-count (9.81), exceeded the t-table (1.671), indicating a significant difference between the two groups. These results demonstrate that VSS, when applied to specific vocabulary categories and competency levels, could improve students’ vocabulary mastery. Overall, integrating VSS effectively improved students’ vocabulary mastery by encouraging active participation and recommending its integration into instruction.